The Influence Of Promotion, Price And Product On Customer Satisfaction Alfamart Letnan Jahidin Manna South Bengkulu - Sartika, Sartika; Indriasari, Nia; Rahman, Abdul (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
This study aims to analyze the effect of promotions, prices, and products on customer satisfaction. This research was conducted on Alfamart customer Letnan Jahidin, South Bengkulu. The analytical method used in this study is quantitative method. In this study, the scale making technique used Likert scale technique. The data processing method used by researchers is multiple regression analysis. The sample used in this study was 150 respondents. Sampling method using accidental sampling method. The data obtained is primary data which is the result of respondents' answers to the questionnaires distributed. The results showed that the promotion variable partially had a significant effect on customer satisfaction, the price variable partially had a significant effect on customer satisfaction, the product variable partially had a significant effect on customer satisfaction, and three independent variables namely promotion, price, and product significantly contributed to the customer satisfaction variable. The adjusted R square results found that the effect of promotion, price, and location on customer satisfaction could be explained by 71,2%, while the remaining 28,8% was explained by other variables that were not included in this research model. From the calculation, the Fcalculate value is 120,473, because the Fcalculate value (120,473) > the Ftable value (2.67), it can be concluded that three independent variables, namely promotion, price, and product, significantly contribute greatly to the variable of customer satisfaction.